A Study of Aviatrixes Holding Leadership Roles in the Historical Phases of Aeronautics - Kemik, Sevdiye; Sahin, Didem Rodoplu; Aslan, Mustafa (Routledge Journals, Taylor & Francis Ltd, 2024)
[Abstract Not Available]
Keywords: Women